2008
DOI: 10.1002/chin.200901010
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Superconductivity and Crystal Structures of (Ba1‐xKx)Fe2As2 (x = 0—1).

Abstract: Superconductors D 8000Superconductivity and Crystal Structures of (Ba1-xKx)Fe2As2 (x = 0-1). -The title compounds are synthesized from stoichiometric mixtures of the elements (Al 2 O 3 crucibles, Ar, 823-1223 K) and characterized by powder XRD and electrical resistance measurements. The XRD patterns at room temperature are indexed with tetragonal body-centered unit cells according to the ThCr2Si2-type (space group I4/mmm) or with orthorhombic face-centered unit cells (space group Fmmm). Superconductivity occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
52
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 24 publications
4
52
0
Order By: Relevance
“…6,7 The AeFe 2 As 2 phases become superconducting ͑maximum T c ϳ 37 K͒ with appropriate substitution of Ae atoms with alkali metals. 8,9 It was also found that isostructural compounds KFe 2 As 2 and CsFe 2 As 2 with formal ͑Fe 2 As 2 ͒ 1− layers were superconducting, having much lower T c 's of 3.8 and 2.6 K, respectively. 9 Moreover, the evolution from a superconducting state to a spin-density wave ͑SDW͒ state by chemical substitution was observed in K 1−x Sr x Fe 2 As 2 .…”
mentioning
confidence: 96%
“…6,7 The AeFe 2 As 2 phases become superconducting ͑maximum T c ϳ 37 K͒ with appropriate substitution of Ae atoms with alkali metals. 8,9 It was also found that isostructural compounds KFe 2 As 2 and CsFe 2 As 2 with formal ͑Fe 2 As 2 ͒ 1− layers were superconducting, having much lower T c 's of 3.8 and 2.6 K, respectively. 9 Moreover, the evolution from a superconducting state to a spin-density wave ͑SDW͒ state by chemical substitution was observed in K 1−x Sr x Fe 2 As 2 .…”
mentioning
confidence: 96%
“…For the 1/T1 NMR spin relaxation rate, the inter-band contribution is consistent with the current experimental results, including a (nonuniversal) T 3 behavior and the absence of a coherence peak. However, the intra-band contribution is considerably larger than the inter-band contributions and still exhibits a small enhancement in the NMR spin relaxation rate right below Tc in the clean limit.Introduction -The recent discovery of iron-based superconductors with a transition temperature as high as 55K has stimulated a flurry of experimental and theoretical activity 2,3,4,5,6,7,8,9,10,11 . However, a conclusive observation of the pairing symmetry still remains elusive, with both nodal and nodeless order parameters reported in experimental observations.…”
mentioning
confidence: 99%
“…Introduction -The recent discovery of iron-based superconductors with a transition temperature as high as 55K has stimulated a flurry of experimental and theoretical activity 2,3,4,5,6,7,8,9,10,11 . However, a conclusive observation of the pairing symmetry still remains elusive, with both nodal and nodeless order parameters reported in experimental observations.…”
mentioning
confidence: 99%
“…The emergence of (Ba,Sr) 1−x K x Fe 2 As 2 (FeAs-122) [17,18] hole-doped superconductors with transition temperature T c up to 38 K has enriched the research in this area. Although stoichiometric (undoped) BaFe 2 As 2 shares the same feature with undoped LnFeAsO of a spin density wave type magnetic order and a structural transition at similar temperatures [19,20], however, there are also some significant differences between the properties of FeAs-1111 and FeAs-122 superconductors.…”
mentioning
confidence: 99%
“…[23], in superconductors with low superfluid density (ρ s ), T c scales linearly with ρ s ∝ λ −2 ab (0), this is actually not required by the BCS theory. However, it is found that the charge carrier density in FeAs-122 is an order of magnitude larger than those in FeAs-1111 systems [17,24]. Thus it is very interesting to know whether the Uemura plot is still satisfied in FeAs-122 superconductors.…”
mentioning
confidence: 99%